2015
DOI: 10.1016/j.plaphy.2015.10.021
|View full text |Cite
|
Sign up to set email alerts
|

Salt stress-induced production of reactive oxygen- and nitrogen species and cell death in the ethylene receptor mutant Never ripe and wild type tomato roots

Abstract: The salt stress triggered by sublethal, 100 mM and lethal, 250 mM NaCl induced ethylene production as well as rapid accumulation of superoxide radical and H2O2 in the root tips of tomato (Solanum lycopersicum cv. Ailsa Craig) wild type and ethylene receptor mutant, Never ripe (Nr/Nr) plants. In the wild type plants superoxide accumulation confined to lethal salt concentration while H2O2 accumulated more efficiently under sublethal salt stress. However, in Nr roots the superoxide production was higher and unexp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 48 publications
(69 reference statements)
0
39
0
1
Order By: Relevance
“…NaCl treatments may elevate the production of ROS resulting from photosynthesis, respiration and NADPH oxidase (Poór et al , You and Chan ). Antioxidative enzymes provide plant cells with a highly efficient machinery for scavenging the ROS and tightly control the equilibrium of antioxidant system in plant.…”
Section: Discussionmentioning
confidence: 99%
“…NaCl treatments may elevate the production of ROS resulting from photosynthesis, respiration and NADPH oxidase (Poór et al , You and Chan ). Antioxidative enzymes provide plant cells with a highly efficient machinery for scavenging the ROS and tightly control the equilibrium of antioxidant system in plant.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the mutants were more sensitive to salt stress than the wild type. These changes can be attributed to a stronger ionic stress due to K +  loss from the root tissues (Poóra et al 2015). Villalta et al (2008) suggested that several genes located in chromosome 7 of tolerant tomato plants are responsible for governing the active mechanism of Na + /K  +   regulation.…”
Section: Discussionmentioning
confidence: 99%
“…The inconsistent results of SlHK5 , SlRR1 , and SlPRR5 between expression profiles and promoter analyses were also observed in soybean and Chinese cabbage [10,23]. Plant TCS elements were determined to play vital roles in responses to abiotic stresses, particularly drought, high salinity, and high or low temperature in Arabidopsis, rice, tomato, and soybean [11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,42,43]. Tomato LE-ETR3 ( Nr ) participated in salt and heat stresses, and reducing expression of LE-ETR4 led to an enhanced hypersensitive response [24,42,43].…”
Section: Discussionmentioning
confidence: 99%